Die Büchse der Pandora - Pabst, Georg Wilhelm (Germany, 1928)
Originally released in 1928, G. W. Pabst's erotic adaptation of Frank Wedekind's "Lulu" plays was mutilated by censors and reviled by critics of the era. Today's restoration of "Pandora's Box" reveals a masterpiece of the silent era, a momentous meeting of director and star. For the role of Lulu, a destroyer of men who is ultimately destroyed by Jack the Ripper, the German director rejected a young Marlene Dietrich in favor of American actress Louise Brooks, the epitome of the modern woman of the 1920s. Together they produced a startling sex tragedy and an unorthodox femme fatale who is the true victim - of her own carnality and German upper-class morality/ Gazing through the camera, Brooks projects the animal beauty of a a woman who sees the world as her sexual playground, unconscious of the havoc she wrecks on the lives of her lovers. Pabst grips the viewer with an almost violent tension, a passion for reliasm, and an uncompromising treatment of sexual themes.
Duration: 01:50:00
With intertitles in English
Keywords: Fiction films